Synthesis of Benzofuran Derivatives through Cascade Radical Cyclization/Intermolecular Coupling of 2‐Azaallyls. Issue 9 (29th January 2019) - Deng, Guogang; Li, Minyan; Yu, Kaili; Liu, Chunxiang; Liu, Zhengfen; Duan, Shengzu; Chen, Wen; Yang, Xiaodong; Zhang, Hongbin; Walsh, Patrick J.
Abstract: Benzofurans are among the most popular structural units in bioactive natural products, however, the synthesis of such structures by radical cyclization cascade reactions is rare. Herein, we report a mild and broadly applicable method for the construction of complex benzofurylethylamine derivatives through a unique radical cyclization cascade mechanism. Single‐electron transfer (SET) from 2‐azaallyl anions to 2‐iodo aryl allenyl ethers initiates a radical cyclization that is followed by intermolecular radical–radical coupling. This expedient approach enables the synthesis of a range of polycyclic benzofurans that would otherwise be difficult to prepare. Abstract : Well behaved radicals : a mild and broadly applicable method for the construction of complex benzofurylethylamine derivatives through a unique radical cyclization cascade mechanism is presented. SET from 2‐azaallyl anions to 2‐iodo aryl allenyl ethers initiates a radical cyclization that is followed by intermolecular radical–radical coupling.